(untitled) (LACCEI, 2024)
The following investigation is of an applied type of experimental design and diagnosis, which had the objective of analyzing and presenting the improvements that were obtained in the areas of maintenance and logistics of said company by applying the tools of QFD, FMEA, DMAIC and SIX SIGMA to improve the profitability of an automotive company. When carrying out the analysis with the help of the Ishikawa diagram, it ends up that there are 5 main problems that are the following: Lack of training for personnel, Lack of care in the transport of the units, Lack of control in the inspection time of the units arrivals, Lack of inventory control and warehouse order and lack of stock of materials, which will be repaired, carry out the diagnosis with the Pareto diagram for the initial analysis and with the help of control charts in Minitab and will be drawn to represent the current situation and the improvements when applying the tools. The results show that in the maintenance area there was an increase in profitability of 74% and in the logistics area 66%, thus advancing an economic benefit of S/. 17,371.90 and the Go of S/. 1,902.27, an IRR of 22.41% and B/C of 1.4.